2017
DOI: 10.3386/w23119
|View full text |Cite
|
Sign up to set email alerts
|

Global Inequality Dynamics: New Findings from WID.world

Abstract: This paper presents new findings on global inequality dynamics from the World Wealth and Income Database (WID.world), with particular emphasis on the contrast between the trends observed in the United States, China, France, and the United Kingdom. We observe rising top income and wealth shares in nearly all countries in recent decades. But the magnitude of the increase varies substantially, thereby suggesting that different country-specific policies and institutions matter considerably. Long-run wealth inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
342
1
48

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(406 citation statements)
references
References 8 publications
(12 reference statements)
3
342
1
48
Order By: Relevance
“…The instrument matrix is restricted to lag 2. * p < 0.1, ** p < 0.05, *** p < 0.01 Alvaredo et al (2015). Due to the small number of observations, the regressions exclude period fixed effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument matrix is restricted to lag 2. * p < 0.1, ** p < 0.05, *** p < 0.01 Alvaredo et al (2015). Due to the small number of observations, the regressions exclude period fixed effects.…”
Section: Resultsmentioning
confidence: 99%
“…Data concerning the development level, fertility, unemployment, age dependency, and the quintiles and deciles of the income distribution are extracted from World Bank (2014), POLRIGHT stems from Freedom House (2014), and TOP-1 is taken from SWIID 4.0, which is the latest version covering data on the income share of the top 1 percent. Due to potential concerns about the data quality of version 4.0 of the SWIID, we analyze robustness of our results using data on top incomes from the World Wealth and Income Database (WID), compiled by Alvaredo et al (2015). In addition, as data regarding the shape of the income distribution is partly from World Bank and partly stems from the SWIID, Figure (A1) in the appendix conducts a consistency check between inequality measures of both sources.…”
Section: Empirical Model and Estimation Techniquementioning
confidence: 99%
“…His first calculations stopped in 2008 (he later provided new data up to 2012), just when the Great Recession started, Nonetheless, Alvaredo et al (2018), in their World Inequality Report have confirmed Milanovic's findings and have shown that the crisis has only increased this trend, putting even more pressure on the middle classes in the US and Europe, which suffered to a greater extent the effects of the global financial and euro crises.…”
mentioning
confidence: 48%
“…Meanwhile, the bottom 50% only received half of that, or 12% of total income growth. 50 For someone in the bottom 10%, their average annual income has risen less than $3 in a quarter of a century. This is a deeply inefficient way to eliminate poverty, with just 13 cents in each dollar of global income growth going to the bottom 50%, and 42 cents going to the top 10%.…”
Section: Inequality and Povertymentioning
confidence: 99%
“…According to the World Inequality Report 2018, between 1980 and 2016 the top 1% received 27 cents of each dollar from global income growth -more than twice the bottom 50%, who only secured 12 cents of every dollar. 177 Economist David Woodward has calculated that given the distribution of global income growth, it will take between 123 and 209 years to get to the point where everyone on earth is living on more than $5 a day. This would require global production and consumption to be 175 times bigger than they are today.…”
Section: Reductions In Povertymentioning
confidence: 99%